Quelle gouvernance des projets d’ouverture et d’extension de carrières ? - Anne-Cécile Jacquot (Projets de Paysage)
The creation and expansion of solid rock quarries, gravel pits or sandpits often generate local debate around the question of landscapes that are modified. This article is based on surveys of actors involved in the opening and expansion of quarries. It was drafted in the context of achieving a quarry landscapes guide for the Union nationale des industries de carrières et matériaux de construction (National Union of Quarry Industries and Building Materials) (Unicem). It outlines and discusses what public and private actors are arguing. They are involved in projects not only to enforce existing regulations, but also to offer with residents and elected officials to create new landscapes during and after the extraction.